Hypergamy reconsidered: Marriage in England, 1837-2021. - Gregory Clark; Neil Cummins (PLoS ONE)
It is widely believed that women value social status in marital partners more than men, leading to female marital hypergamy ("marrying up"), and more female intergenerational social mobility. Using evidence from more than 33 million marriages and 67 million births in England 1837-2021 we show that within this era there was never significant hypergamous marriage by women. The average status of women's fathers equaled that of their husbands' fathers. For marriages 1912-2007 the average social status of female surnames equaled that of male. This was true also for parent surnames of children. Consistent with this, there was no differential tendency in England of men and women to marry by family status. There is also ancillary evidence that physical attraction cannot have been the significant determinant of matching in marriages in any period 1837-2021, based on the very strong correlation observed in underlying social status for marital partners throughout these years.